Factors influencing fluctuation in Malaysia palm oil price / Fatin Asmaa Abdullah - Abdullah, Fatin Asmaa (2014)
Malaysia is the second largest producers of palm oil in the world after Indonesia. This research study is to investigate the factors influencing the instability and fluctuation of palm oil price. The dependent variables in this research study are the exchange rate in USD, the crude oil price, the soybean oil price and the exports of palm oil. In detail, the data was collected from official website of World Bank, inflation data and index mundi for 48 years (1964-2012) in yearly basis that has been analyzed using the time series analysis. As a result, the crude oil price, soybean oil price and exports have positive relationships in the long run with palm oil price. In the other hand, exchange rate shows a negative relationship towards palm oil price.